Social Science Learning Media Prototype Based on Smartphone in the 4.0 Learning Era - Sari, Jeryy Puspita; Suyahmo, Suyahmo; Juhadi, Juhadi (Universitas Negeri Semarang, 2021)
Smartphone-based learning media is an alternative development of learning media that can penetrate the limitations of space and time. The purpose of this study is to determine the prototype model of smartphone-based learning media for learning in the 4.0 era. This study was done in SMAN 1 Jepon, Kabupaten Blora.used Mixed Methods method. Mixed Method is a combination of quantitative and qualitative, with a sequential mixed methods strategy. Qualitative data were obtained through in-depth interviews and participatory observation. while quantitative data is obtained by filling out a questionnaire. The results of this study were that most students answered pleasant, easy to understand, interesting, practical, and not boring. This is because there is interesting music and animation. The percentage of the Minimum Criteria of Mastery Learning is 91.4% of 36 students and there are only 3 students who have not completed it. Using learning media that is fun and easy to understand is very helpful for students to learn to face challenges in the 4.0 era.